2015
DOI: 10.5539/res.v7n11p348
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recruitment and Selection Practices in the Organizational Performance of Iraqi Oil and Gas Sector: A Brief Literature Review

Abstract: Oil and gas sector forms the backbone of Iraqi economy with more than 80 percent of all businesses in Iraq related to oil and gas. The sector also employs a bulk of the workforce, playing a crucial part in economic and social development in Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
11
0
1
Order By: Relevance
“…Several researchers examine the effect of recruitment and section (Chand & Katou, 2007; Saddam & abu Mansor, 2015), and in their robust research identified the impact of RS on organizational performance. Although, Katou and Budhwar (2007) elaborate the effect of human resources practices and the impact of organizational incentives and organizational performance.…”
Section: Theoretical Background Hypotheses and Research Modelmentioning
confidence: 99%
“…Several researchers examine the effect of recruitment and section (Chand & Katou, 2007; Saddam & abu Mansor, 2015), and in their robust research identified the impact of RS on organizational performance. Although, Katou and Budhwar (2007) elaborate the effect of human resources practices and the impact of organizational incentives and organizational performance.…”
Section: Theoretical Background Hypotheses and Research Modelmentioning
confidence: 99%
“…The better the recruitment and selection process, the better the performance. This finding is reinforced by the research conducted by Saddam and Mansor (2015) who found that effective recruitment and selection practices in companies-related to performance-will increase labor productivity, product quality, organizational innovation. Study conducted by Ekwoaba et al (2015) also stated that recruitment and selection can improve employee performance.…”
Section: The Results Of Ahp Analysis Testmentioning
confidence: 94%
“…Estudios previos muestran que una insuficiente o inadecuada gestión de los trabajadores provoca mayores tasas de rotación y menor productividad y es una importante causa de fracaso empresarial. Por tanto, disponer de sistemas de RRHH efectivos ayuda a la organización a atraer y contratar a los mejores candidatos, los cuales pueden lograr mejoras cuantitativas y cualitativas para la consecución de los objetivos empresariales (Saddam y Mansor, 2015).…”
Section: Prácticas De Reclutamiento-selección Y Resultados Organizativosunclassified